Tristetraprolin, a Potential Safeguard Against Carcinoma: Role in the Tumor Microenvironment - Zhang, Diwen; Zhou, Zhigang; Yang, Ruixia; Zhang, Sujun; Zhang, Bin; Tan, Yanxuan; Chen, Lingyao; Li, Tao; Tu, Jian (Frontiers in Oncology, 2021)
Tristetraprolin (TTP), a well-known RNA-binding protein, primarily affects the expression of inflammation-related proteins by binding to the targeted AU-rich element in the 3’ untranslated region after transcription and subsequently mediates messenger RNA decay. Recent studies have focused on the role of TTP in tumors and their related microenvironments, most of which have referred to TTP as a potential tumor suppressor involved in regulating cell proliferation, apoptosis, and metastasis of various cancers, as well as tumor immunity, inflammation, and metabolism of the microenvironment. Elevated TTP expression levels could aid the diagnosis and treatment of different cancers, improving the prognosis of patients. The aim of this review is to describe the role of TTP as a potential safeguard against carcinoma.